2017
DOI: 10.18632/oncotarget.16401
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a combination of serum IgG and IgA antibodies against selected mycobacterial targets provides promising diagnostic signatures for active TB

Abstract: Immunoglobulin G (IgG) based tests for the diagnosis of active tuberculosis (TB) disease often show a lack of specificity in TB endemic regions, which is mainly due to a high background prevalence of LTBI. Here, we investigated the combined performance of the responses of different Ig classes to selected mycobacterial antigens in primary healthcare clinic attendees with signs and symptoms suggestive of TB. The sensitivity and specificity of IgA, IgG and/or IgM to LAM and 7 mycobacterial protein antigens (ESAT-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 40 publications
2
20
0
4
Order By: Relevance
“…This interest in humoral immunity in Mtb is evidenced by a mounting number of studies that have identified specific antibody targets, and structural or functional differences that are observed during different TB disease states (26)(27)(28)(29)(30). For example, while Mtb-specific IgG titers alone have been insufficient in distinguishing between latent and active TB, refinement of these correlates using additional isotypes, subclasses, and other Fc modifications are underway (see Figure 1) (31)(32)(33)(34)(35). Moreover, incorporating data including multiple instead of single Mtb antigens as well as Fab affinity and avidity to Mtb targets may improve sensitivity and specificity (36)(37)(38)(39)(40).…”
Section: Introductionmentioning
confidence: 99%
“…This interest in humoral immunity in Mtb is evidenced by a mounting number of studies that have identified specific antibody targets, and structural or functional differences that are observed during different TB disease states (26)(27)(28)(29)(30). For example, while Mtb-specific IgG titers alone have been insufficient in distinguishing between latent and active TB, refinement of these correlates using additional isotypes, subclasses, and other Fc modifications are underway (see Figure 1) (31)(32)(33)(34)(35). Moreover, incorporating data including multiple instead of single Mtb antigens as well as Fab affinity and avidity to Mtb targets may improve sensitivity and specificity (36)(37)(38)(39)(40).…”
Section: Introductionmentioning
confidence: 99%
“…Um trabalho sul-africano analisou a Imunoglobulina A (IgA) e IgM contra 10 Ag distintos do Mtb. Sendo estes: Lipoarabinomanana (LAM), 7 Ag micobacterianos proteicos (ESAT-6, Tiol peroxidase (Tpx), Proteína de ligação a fosfato 1 (PstS1), Alanina Desidrogenase (AlaDH), MPT64, proteínas de 16 kDa (também referido na literatura como Hsp16.3) e 19 kDa (p19)) e 2 combinações de Ag (TUB (PstS1, 16 kDa, APA), TB-LTBI (Tpx, L16)) (AWONIYI et al, 2017).…”
Section: Biomarcadores Para Diagnóstico Da Doençaunclassified
“…Não obstante, em perfis sorológicos utilizando múltiplos biomarcadores a acurácia para distinção tanto no contexto TB vs. ORD como TB vs. LTBI foi significativamente melhorada, alcançando valores próximos a 100%. Todavia, volta-se ao ponto das limitações inerentes ao delineamento do trabalho, carecendo estudos de maior proporção para fundamentar (ou não) seus dados (AWONIYI et al, 2017).…”
Section: Biomarcadores Para Diagnóstico Da Doençaunclassified
See 2 more Smart Citations